Emotional and behavioral influence of headache in Pediatric rheumatic diseases - Dogangun, Burak; Taysanli, Mustafa Emir; Sen, Ezgi; Guntel, Murat; Kasapcopur, Ozgur; Sohtaoglu, Melis; Uluduz, Derya (Elsevier Sci Ltd, 2017)
[Abstract Not Available]
Keywords: Young-Adults; Children; Migraine; Adolescents; Psychopathology; Prevalence; Schoolchildren; Metaanalysis; Depression